2009
DOI: 10.1007/s00059-009-3252-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Access Site Complications after Percutaneous Transfemoral Aortic Valve Implantation

Abstract: Completely percutaneous TAVI has a high acute success rate with low intraprocedural and 30-day mortality. The patient collective appears to be prone to vascular complications which remain an important limitation of this novel technique. Although conservative or endovascular management is possible in the majority of cases, further technological developments are obliged to reduce the vascular complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 34 publications
0
49
0
6
Order By: Relevance
“…However, despite the less invasive approach, serious adverse events including major vascular complications are still reported with an incidence of 7-15% [5][6][7]. Although vascular complications may affect procedural results, contributing factors have not been well defined [8,9]. Therefore, the purpose of this study was to record the incidence and identify angiographic predictors of vascular complications after TAVI, in patients in whom vascular access-site closure was exclusively performed with the Prostar device.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the less invasive approach, serious adverse events including major vascular complications are still reported with an incidence of 7-15% [5][6][7]. Although vascular complications may affect procedural results, contributing factors have not been well defined [8,9]. Therefore, the purpose of this study was to record the incidence and identify angiographic predictors of vascular complications after TAVI, in patients in whom vascular access-site closure was exclusively performed with the Prostar device.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular complications are not rare in TAVI by the transfemoral approach and can significantly affect the overall clinical outcome [8][9][10] . At the end of the TAVI procedure, a control angiography obtained from the contralateral femoral access site allows early identification of vascular access site complications.…”
Section: Resultsmentioning
confidence: 99%
“…A series of vascular complications are commonly reported to be associated with TAVI, including arterial perforation, dissection, pseudoaneurysm, stenosis/occlusion and arterio-venous fistula [7][8][9][10] . The VARC, a collaboration between academic research organizations in the United States and Europe, has elaborated a consensus document on TAVI related endpoint definitions [36] and a more recent updated document [37] , in which a classification of major and minor vascular access complications has been proposed ( Table 1).…”
Section: Vascular Access Site Complications After Tavi and Their Manamentioning
confidence: 99%
See 1 more Smart Citation
“…These complications most frequently occur in the iliofemoral region. In previous studies, TAVI-induced vascular complication rates were reported to be 1.9%-17.3% (21,22,31) . In our study, however, vascular complication occurred in a total of 18 (16.4%) patients.…”
Section: Percutaneous Closure Device Failurementioning
confidence: 98%